Efficient method for the synthesis of methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate - Salunke, D. B.; Hazra, Braja G.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Pore, V. S. (Tetrahedron, 2005)
The synthesis of methyl 11 alpha-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate, methyl 11 beta-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate and methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate have been achieved. Mechanistic aspects for the decomposition of steroidal azidoketones to its enamines are discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 11-aminosteroid; 11-azidosteroid; base catalyzed epimerization; HIV-1 protease inhibitors; steroidal enamines

Stereoselective synthesis of (2R, 3S, 22R, 23E)-6, 6-ethylenedioxy-22-hydroxy-2, 3-isopropylidenedioxy-24-methyl-5 alpha-cholest-23-ene: An intermediate for the synthesis of castasterone, dolichosterone and brassinolide - Hazra, Braja G.; Kumar, T. P.; Pore, V. S. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2005)

Amino functionalized novel cholic acid derivatives induce HIV-1 replication and syncytia formation in T cells - Salunke, Deepak B.; Ravi, D. S.; Pore, V. S.; Mitra, Debashis; Hazra, Braja G. (Journal of Medicinal Chemistry, 2006)
Synthesis of C-11 azido/amino functionalized cholic acid derivatives has been achieved in excellent yields. Contrary to the previous prediction of analogous compounds to be HIV-1 protease inhibitors, in the present study these novel cholic acid derivatives induced host cell fusion during the progress of HIV-1 infection and produced multinucleated giant cells. This is the first report of syncytia induction and enhancement of viral replication in HIV-1 infected T cells by cholic acid derivatives.

Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Syntheses of 1,2-amino alcohols and their applications for oxazaborolidine catalyzed enantioselective reduction of aromatic ketones - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S. (Australian Journal of Chemistry, 2007)
Six new chiral 1,2-amino alcohol derivatives have been synthesized starting from (1R, 2R)-2-amino-1-phenylpropane-1,3- diol. Asymmetric reduction of aryl ketones with in-situ generated oxazaborolidine from these amino alcohol derivatives and BH3 center dot Me2S afforded secondary alcohols with good yield and moderate to high enantiomeric excess.

Molecular association via halogen bonding and other weak interactions in the crystal structures of 11-bromo-12-oxo-5 beta-cholan derivatives - Salunke, Deepak B.; Hazra, Braja G.; Gonnade, Rajesh G.; Pore, Vandana S.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Methyl 3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 2, methyl 11 alpha-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 3, methyl 11 beta-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 4 and methyl 11,11-dibromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 5 were synthesized. The crystal structures of these molecules were resolved to study the effect of bulky bromine atom in the steroid skeleton of cholic acid with different stereo-chemical orientations at C-11 on the two-dimensional arrangement of molecules and solid-state properties. All the molecules associate only via weak intermolecular interactions in their crystal structures, notable one being the Halogen Bonded assembly (C-Br center dot center dot center dot O) in 5. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 11-Bromosteroids; Cholic acid; crystal structure; Halogen bonding

Synthesis and antimicrobial activity of beta-lactam-bile acid conjugates linked via triazole - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Chavan, Pradnya S.; Deshpande, Mukund V. (Bioorganic & Medicinal Chemistry Letters, 2008)
Synthesis of novel 1,2,3-triazole-linked beta-lactam-bile acid conjugates 17-24 using 1,3-dipolar cycloaddition reaction of azido beta-lactam and terminal alkyne of bile acids in the presence of Cu( I) catalyst ( click chemistry) have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and moderate antibacterial activity against all the tested strains. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.

Synthesis of chimeric tetrapeptide-linked cholic acid derivatives: impending synergistic agents - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Dodd, Robert H.; Thierry, Josiane; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit (Bioorganic & Medicinal Chemistry Letters, 2008)
Tetrapeptides derived from glycine and beta-alanine were hooked at the C-3 beta position of the modified cholic acid to realize novel linear tetrapeptide-linked cholic acid derivatives. All the synthesized compounds were tested against a wide variety of microorganisms (Gram-negative bacteria, Gram-positive bacteria and fungi) and their cytotoxicity was evaluated against human embryonic kidney (HEK293) and human mammary adenocarcinoma (MCF-7) cell lines. While relatively inactive by themselves, these compounds interact synergistically with antibiotics such as fluconazole and erythromycin to inhibit growth of fungi and bacteria, respectively, at 1-24 mu g/mL. The synergistic effect shown by our novel compounds is due to their inherent amphiphilicity. The fractional inhibitory concentrations reported are comparable to those reported for Polymyxin B derivatives. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial activity; Cholic acid; Cytotoxicity; Synergism; Tetrapeptide

Exploration of click reaction for the synthesis of modified nucleosides as chitin synthase inhibitors - Chaudhary, Preeti M.; Chavan, Sayalee R.; Shirazi, Fazal; Razdan, Meenakshi; Nimkar, Prachi; Maybhate, Shailaja P.; Likhite, Anjali P.; Gonnade, Rajesh G.; Hazra, Braja G.; Deshpande, Mukund V.; Deshpande, Sunita R. (Bioorganic & Medicinal Chemistry, 2009)
Click reaction approach toward the synthesis of two sets of novel 1,2,3-triazolyl linked uridine derivatives 19a-19g and 21a-21g was achieved by Cu(I)-catalyzed 1,3-dipolar cycloaddition of 5'-azido-5'-deoxy-2',3'-O-(1-methylethylidene) uridine (17) with propargylated ether of phenols 18a-18g and propargylated esters 20a-20g. Structure of one of the representative compound 19d was unambiguously confirmed by X-ray crystallography. Chitin synthase inhibition study of all these compounds 19a-19g and 21a-21g was carried out to develop antifungal strategy. Compounds 19d, 19e, 19f, and 21f were identified as potent chitin synthase inhibitors by comparing with nikkomycin. Compounds 19a, 19b, 19c, 19d, 21a, and 21b showed good antifungal activity against human and plant pathogens. Compounds 19a, 19b, 19f, 21c, 21f, and 21g were identified as lead chitin synthase inhibitors for further modi. cations by comparing results of inhibition of growth, % germ tube formation and chitin synthase activity. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-dipolar cycloaddition; 3-Triazole; 4-Disubstituted-1; 5 `-Azidouridine; Antifungal compounds; Chitin synthase activity; Click reaction; Uridine nucleosides

Pd-catalyzed one-pot chemoselective hydrogenation protocol for the preparation of carboxamides directly from azides - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Thierry, Josiane; Dodd, Robert H. (Tetrahedron Letters, 2010)
Carboxamides were obtained efficiently in high yields from azides on reaction with the corresponding pre-formed activated carboxylic acids in a single-step reductive transformation using hydrogen atmosphere (balloon) under Pd/BaSO(4) or Pd/CaCO(3) catalysis. The method is highly chemoselective and compatible with extremely labile functional groups such as benzyl carbamates, benzyl ethers, benzyl esters, and olefins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Azide; Carboxamide; Catalytic hydrogenation; Chemoselective; Palladium; Succinimide ester

RuCl3-TBHP mediated allylic oxidation of Delta(8(9)) lanosterol derivatives - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S. (Tetrahedron Letters, 2011)
A variety of Delta(8(9))-lanosterol derivatives were converted into 7,11-dienones using t-butyl hydroperoxide in the presence of ruthenium chloride (RuCl3) in good yields. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; Oxygenated steroids; Ruthenium chloride; Steroidal ketones; t-Butyl hydroperoxide

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids

Concise account of various approaches for stereoselective construction of the C-20(H) stereogenic center in steroid side chain - Shingate, Bapurao B.; Hazra, Braja G. (Chemical Reviews, 2014)

Ionic hydrogenation-directed stereoselective construction of C-20(H) stereogenic center in steroid side chains: Scope and limitations - Shingate, Bapurao B.; Hazra, Braja G. (Tetrahedron, 2017)
Stereoselective synthesis of steroidal C-20 tertiary alcohols with n-butyl, vinyl, furyl, thienyl, thiazolyl, aryl and pyridyl side chains via Grignard reaction or organolithium reagents have been realized starting from readily available 16-dehydropregnenolone acetate. The ionic hydrogenation of steroidal C-20 tertiary alcohols having furyl, methylfuryl, thienyl, phenyl and 4-methoxyphenyl side chains, resulted into the deoxygenated product with C-20 natural configuration in excellent yields. However, the alkyl, thiazolyl and pyridyl incorporated steroidal C-20 tertiary alcohols were failed under the same reaction condition. The scope of ionic hydrogenation is further highlighted through the stereoselective reduction of steroidal C-20,21-ene compounds with furyl, thienyl and 4-methoxyphenyl side chains gave the saturated compounds with C-20 natural configuration